AN EXPANSION OF CONCEPT THE STATE ECONOMIC LOSS IN CORRUPTION IN INDONESIA - Supriyanto Supriyanto; Hartiwiningsih Hartiwiningsih; Supanto Supanto (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
This research aimed to analyze the meaning of state finance loss in corruption and provide prescriptions the expansion of concept the state economic loss in Corruption Eradication Acts in Indonesia. This research was a normative-legal approach with the approaches of statute, case, comparative and conceptual. Legal materials were analyzed by syllogism of induction, deduction and interpretation. The research indicates that, first, the meaning of state economic in corruption is a life of economic that structured as a joint venture based on kinship principles, in this case is a cooperative, or other entity that has the principles and spirit of mutual cooperation, kinship and joint ventures, so if there are irregularities in cooperatives or other business entities principled and cooperative spirit that resulted in losses, it can be applied to corruption. But this has never happened in the practice of corruption law enforcement. Secondly, the need for expansion the concept of state economy in corruption crime, thus acts in state economy loss, among others: the implementation of construction without indepth study (feasibility study) so it does not have the value of benefits, contractor is unable to finish the government’s work in accordance with employment contracts so that work is not finish and not function, basic materials stockpiling and public’s needs (stockpiling of food, fuel, fertilizer, etc.), import policies that harm the public’s production and acts that damage the ecological of environment (forestry, mining and fisheries conducted unlawfully). Keywords: expansion, the concept of state economy, corruption.